INTERROGATING THE IMPLEMENTATION OF THE CONTRIBUTORY PENSION SCHEME IN NIGERIA - Cletus Adeyemoh Olunde (International Studies Journal)
The failure of the Defined Benefit Scheme implemented by government over the years makes the introduction of the Contributory Pension Scheme a welcomes development as it has ensured that retirees in the country no longer die while waiting endlessly for their retirement benefits that in most cases would never materialize. Following the implementation of the scheme in 2004, a total of 269,143 employees have so far retired from the scheme and are currently on the Programmed Withdrawal package. This milestone has no doubt made the scheme one of the preferable options in pension fund administration due to the level of transparency and safety of the contributors' funds compared to the bottlenecks, irregularities and corruption witnessed under the Defined Benefit Scheme in Nigeria. However, these milestones are not without some challenges, which will be the basis of this paper. The paper adopted quantitative and qualitative research techniques in this paper and it was revealed that there is a delay in pension benefit payment which is negatively affecting the retirees, benefit adequacy issue resulting in poor benefit payment to the retirees and the general poor welfare condition of the retirees currently on the programme withdrawal package of the scheme. It, therefore, recommended amongst others the percentage of pension emoluments on the part of the government should be reviewed upward to further enhance the take-home pay of the retirees in other to address the problem of the benefit adequacy of the Scheme while also addressing issues associated with the delay in pension entitlement payment particularly the accrued right benefit counterpart of their package.